Anticancer Potential of Silibinin Loaded Polymeric Nanoparticles against Breast Cancer Cells: Insight into the Apoptotic Genes Targets - Pourgholi, Ali; Dadashpour, Mehdi; Mousapour, Akram; Amandi, Akram Firouzi; Zarghami, Nosratollah (Asian Pacific Organization for Cancer Prevention, 2021)
Silibinin (SIL) is a natural polyphenolic flavonoid with multiple biological and anti-cancer features. However, the complex hydrophobic nature and inadequate bioavailability of SIL hinder its efficiency at tumor sites. Investigating the possibility of an extensive strategy for better treatment of breast cancer, we carried out a comparative exploration of the inhibitory effect of SIL and SIL loaded PLGA-PEG nanoparticle (SIL-NPs) on the expression of the proapoptotic target genes, which is considered as an influential molecular target for treatment of breast cancer. The main diameter of SIL-NPs was 220 ± 6.37 and 150 ± 23.14 nm via DLS and FE-SEM respectively. Furthermore, the zeta potential of PLGA-PEG and SIL-NPs was -5.48±0.13 and -6.8±0.26 mV respectively. SIL encapsulation efficiency and drug release were determined by about 82.32 % by analyzing the calibration curve of SIL absorbance at 570 nm. Cytotoxicity of SIL and SIL-NPs was conducted by MTT assay after 24, 48, and 72 h of exposure times, and the gene expression levels of apoptotic genes, p53 and hTERT was measured by real-time PCR. Evaluation of drug toxicity revealed that SIL-NPs represents higher cytotoxic effects than pure SIL in a time and dose-dependent manner. Moreover, the results demonstrated that SIL-NPs could induce apoptosis in breast cancer cells by upregulation of caspase-3, caspase-7, p53 and Bax, along with Bcl-2, hTERT, survivin and Cyclin D1 down regulation. Our results indicated that PLGA-PEG can be used as stable carriers in nano-dimensions and SIL-NPs can be considered as a promising pharmacological agent for cancer therapy. © 2021, Asian Pacific Journal of Cancer Prevention. All rights reserved.
Keywords: apoptosis; breast cancer; PLGA-PEG; polymeric nanoparticles; Silibinin